Digital Health Intervention Towards Suicidal Ideation Among Adolescents - Cherol Nelson Ering; Shanti Wardaningsih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Adolescents are a vulnerable group when it comes to mental health issues like suicidal ideation. Digital health, with its increasingly advanced and developing technology in industry 4.0 area, can be an alternative intervention to prevent or even reduce suicidal ideation among adolescents. This article is a literature review that aims to discuss the use of digital health interventions to reduce suicidal ideation among adolescents. The article search method uses a database from Pubmed, Google Scholar, Science Direct, and CrossRef. There were 12 articles that were reviewed. The findings indicated that a digital health intervention can reduce or eliminate suicidal ideation in adolescents. The internet, websites, mobile applications, and messenger are all examples of digital health. The influence of digital health interventions for suicidal ideation comes from benefits of digital health such as screening for suicidal ideation (both by health workers and independently), counseling, psychoeducation, and peer support. Digital health can be used effectively by millennials or teenagers who live in modern times.Abstrak: Remaja merupakan populasi yang rentan mengalami kesehatan mental seperti ide bunuh diri. Digital Health menjadi intervensi pilihan alternatif untuk mencegah bahkan mengurangi ide bunuh diri pada remaja terutama di area industri 4.0 dengan pemanfaatan teknologi yang sudah semakin maju dan berkembang. Penelitian ini merupakan literature review yang bertujuan untuk membahas intervensi digital health terhadap ide bunuh diri pada remaja. Metode pencarian artikel menggunakan database Pubmed, Google Scholar, Science Direct, dan CrossRef. Artikel yang direview berjumlah 12 artikel. Hasil literature review menunjukkan intervensi digital health dapat mengurangi atau mengatasi ide bunuh diri pada remaja. Jenis digital health yang digunakan internet/webisite, mobile application, dan messenger. Adapun manfaat yang dapat diberikan digital health yaitu skrining ide bunuh (baik oleh tenaga kesehatan, dan skrining secara mandiri), konseling, psikoedukasi, dan dukungan teman sebaya. Intervensi Digital Health efektif dapat digunakan kepada kaum generasi milenial atau remaja yang hidup di zaman modern.